Implementasi IoT dan Android untuk Pemantauan dan Pemeliharaan Alat Pelindung Diri K3 di PT Paku Jaya - Rohman, Muhammad Aqifur; Irawan, Denny (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The construction industry has many factors that cause work accidents, but the most highlighted is worker awareness in using Personal Protective Equipment (PPE). This study develops an Internet of Things (IoT)-based monitoring system to maintain the quality of Personal Protective Equipment (PPE) in the storage room by monitoring environmental conditions and officer activities. This system is designed to monitor room temperature, humidity, and air quality to ensure that PPE is stored in standard conditions. In addition, the system is equipped with a Radio Frequency Identification (RFID) module to record and monitor the activities of officers entering and leaving the storage room. The ESP32 microcontroller is used as a data processing center connected to various sensors and RFID modules, and functions to send data in real time to the server via a Wi-Fi network. The test results show that the system is able to monitor room temperature conditions accurately in the range of 20-250C and air humidity at 40-60% and detect officer activities effectively. Indoor dust conditions are maintained below 10 mg/m3 by utilizing a blower fan. This system is expected to support safer, more efficient, and technology-based PPE storage management.